Secondary aspergillus fumigatus infection associated with coloidal goiter in a Black-masked Lovebird (Agapornis personata) - Gonçalves, Guilherme Augusto Marietto [UNESP]; Grandi, Fabrizio [UNESP]; Andreatti Filho, Raphael Lucio [UNESP]; Rocha, Noeme Sousa [UNESP] (My University, 2014)
Aspergillosis is caused by fungus of Aspergillus genus. Is a multifactorial secondary disease and occurs mainly to immunodeficiency. Goiter is the name to non-inflammatory and non-neoplasic thyroid growth which affecting the animal metabolism. In this report we describe a case of aspergillosis and colloidal goiter in a male Black-masked lovebird (Agapornis personata) diagnosed by post mortem exam. The bird was presented for examination due to severe respiratory signs. An initial palliative treatment was performed in order to relieve the symptoms. Despite this, the patient came to die without performing additional ancillary tests. On gross exam, a pulmonary nodule was observed from which we were able to isolate Aspergillus fumigatus on microbial culture. Histological assessment revealed pulmonary aspergilosis and colloid goiter. Based on histopathological and microbiological assessments we conclude that infection probably was secondary to colloid goiter.

Aspergilose é uma doença causada por fungos do gênero Aspergillus. É uma doença secundária de caráter multifatorial e ocorre principalmente por imunodeficiência. O bócio é o nome dado ao crescimento nãoneoplásico e não-inflamatório da tireoide que afeta o metabolismo animal. O presente artigo descreve um caso de aspergilose e bócio coloidal em macho de Agaporne mascarado (Agapornis personata) diagnosticados por exame post mortem. A ave foi atendida com sintomatologia respiratória acentuada, sendo realizado um procedimento clínico inicial para aliviar os sintomas, porém a ave morreu sem que exames auxiliares fossem realizados. Na análise necroscópica foi encontrando a presença de um nódulo no pulmão e foi isolado Aspergillus fumigatus no exame microbiológico. A análise histológica confirmou o quadro de aspergilose e revelou também alterações tiroidianas compatíveis com bócio. Mediante os achados patológicos relacionou-se a ocorrência da infecção devido às alterações metabólicas causadas pelo quadro de bócio.
Keywords: Agapornis personata; Aspergillosis; Goiter; Avian pathology; Agapornis personata; Aspergilose; Bócio; Patologia aviária